ANALISIS PENETAPAN STANDAR BIAYA PENDIDIKAN PADA SMA NEGERI 2 KUALA KABUPATEN NAGAN RAYA - RM. Teguh Eko Atmaja; Cut Zahri Harun; Sakdiah Ibrahim (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2016)
Abstract: Determination of standard cost of education is a criterion for good measure the overall expenditure in the form of cash and non-cash as an expression of the sense of responsibility of all parties (the public, parents, and government) to the development of education in order to achieve educational goals efficiently and effectively. The purpose of this study was to determine the ability of the principal to establish the cost of education, including: (1) Preparation of the cost of education; (2) The use of the cost of education; and (3) Auditing the cost of education. This study used a qualitative approach with descriptive methods, techniques of data collection is done through interviews, observation, and documentation. Subjects were principal, treasurer and inspectorate Nagan Raya. The research found: (1) Preparation of educational costs through Plan Budget (RKA) and Draft Budget Shopping Opinions School (budgets) are discussed in a budget meeting in the DPRK; (2) The use of the cost of the education budget comes from the state budget, and the budget and other sources of educational expenses of parents, private, business, and alumni of the largest education budget priorities is to pay the salaries of teachers / employees, which is between 75-80% of the total budget, and the rest for non-teachers' salaries; and (3) the cost of education is an activity Auditing look carefully, investigate, study, examine and investigate the cost of education, including procedures for investigating its books, one truth in a case, the events that have been recorded, placed on their posting, as well as the receipt of cash flows and goods owned by a school organized by the government and society. It is expected that the inspectorate in order to direct and supervise the principal standard-setting the cost of education on the preparation, use, and effective auditing and efficiency so that the cost of education in school on target.Keywords: Determination of Standard Cost of Education and SupervisionAbstrak: Penetapan standar biaya pendidikan adalah suatu kriteria untuk mengukur keseluruhan pengeluaran baik yang berupa uang maupun bukan uang sebagai ungkapan rasa tanggung jawab semua pihak (masyarakat, orang tua, dan pemerintah) terhadap pembangunan pendidikan agar tujuan pendidikan tercapai secara efesien dan efektif. Tujuan penelitian ini adalah untuk mengetahui kemampuan kepala sekolah dalam menetapkan biaya pendidikan, meliputi: (1) Penyusunan biaya pendidikan; (2) Penggunaan biaya pendidikan; dan (3) Pengauditan biaya pendidikan. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif, teknik pengumpulan data dilakukan melalui wawancara, observasi, dan studi dokumentasi. Subjek penelitian adalah kepala sekolah, bendahara dan inspektorat Kabupaten Nagan Raya. Hasil penelitian ditemukan: (1) Penyusunan biaya pendidikan melalui Rencana Penggunaan Anggaran (RKA) dan Rancangan Anggaran Pendapat Belanja Sekolah (RAPBS) yang dibahas dalam rapat anggaran di DPRK; (2) Penggunaan biaya pendidikan bersumber anggaran pemerintah berasal dari APBN, dan APBD dan sumber biaya pendidikan lainnya dari orang tua, swasta, dunia usaha, dan alumni dengan prioritas anggaran pendidikan terbesar adalah untuk membayar gaji guru/ pegawai, yaitu antara 75-80% dari total anggaran, dan selebihnya untuk non-gaji guru; dan (3) Pengauditan biaya pendidikan merupakan kegiatan melihat dengan teliti, menyelidiki, mempelajari, menelaah dan mengusut biaya pendidikan, termasuk mengusut tata cara pembukuannya, salah benarnya suatu hal, peristiwa yang telah dicatat, ditempatkan pada pos-posnya, serta proses arus penerimaan uang dan barang yang dimiliki oleh suatu sekolah yang diselenggarakan oleh pemerintah maupun masyarakat. Diharapkan kepada inspektorat agar dapat mengarahkan dan mengawasi kepala sekolah penetapan standar biaya pendidikan tentang penyusunan, penggunaan, dan pengauditan secara efektif dan efesiensi sehingga biaya pendidikan di sekolah tepat sasarannya.Kata Kunci: Penetapan Standar Biaya Pendidikan, dan Pengawasan